Mild degradation processes in ZnObased varistors: the role of Zn vacancies - Ponce, Miguel Adolfo (2015)
The effects of a degradation process on the structural and electrical properties of ZnO-based varistors induced by the application of dc bias voltage were analysed. Capacitance and resistance measurements were carried out to electrically characterize the polycrystalline semiconductor before and after different degrees of mild degradation. Vacancies’ changes in the varistors were studied with positron annihilation lifetime spectroscopy. Variations on the potential barrier height and effective doping concentration were determined by fitting the experimental data from impedance spectroscopy measurements. These results indicate two different stages in the degradation process consistent with vacancy-like concentration changes.